2019
DOI: 10.1126/scitranslmed.aaw2614
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring of intratumorally administered cytokines to collagen safely potentiates systemic cancer immunotherapy

Abstract: The clinical application of cytokine therapies for cancer treatment remains limited due to severe adverse reactions and insufficient therapeutic effects. Although cytokine localization by intratumoral administration could address both issues, the rapid escape of soluble cytokines from the tumor invariably subverts this effort. We find that intratumoral administration of a cytokine fused to the collagen-binding protein lumican prolongs local retention and markedly reduces systemic exposure. Combining local admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
166
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(172 citation statements)
references
References 60 publications
6
166
0
Order By: Relevance
“…To avoid this problem, researchers have designed various strategies (Kerkar et al, 2010;Zhang et al, 2015;Zhao et al, 2019) to target IL-12 to tumors. However, unless IL-12 is confined to tumor site, systemic toxicity appears to be unavoidable (Momin et al, 2019). As an IL-12 family of cytokine, IL-27 shares some similarities with IL-12.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid this problem, researchers have designed various strategies (Kerkar et al, 2010;Zhang et al, 2015;Zhao et al, 2019) to target IL-12 to tumors. However, unless IL-12 is confined to tumor site, systemic toxicity appears to be unavoidable (Momin et al, 2019). As an IL-12 family of cytokine, IL-27 shares some similarities with IL-12.…”
Section: Discussionmentioning
confidence: 99%
“…[71] When the drug is retained locally, tumor control efficacy is vastly improved with reduction of adverse effects, as demonstrated in preclinical studies. [72,73,50]…”
Section: Improve Local Drug Retentionmentioning
confidence: 99%
“…Active therapeutic Type of cancer Year Reference Chemotherapy PLLA/PEG4000 implant Etoposide NSCLC 2017 [40] In situ gel-forming PCL-PEG-PCL hydrogel implant Liposomal doxorubicin/rhenium-188-tin colloid HCC 2013 [41] PEG nanotubes Doxorubicin Breast 2018 [42] Liquid crystal polymer microcapsule Temozolomide/doxorubicin Brain metastasis 2014 [43] Lauroyl-gemcitabine nanocapsule hydrogel Gemcitabine Glioblastoma 2016 [44] Iontophoretic delivery Gemcitabine/FOLFIRINOX Regimen Breast/pancreas 2015/2016 [ 45,46] Iontophoretic delivery EGFR-targeted liposomal 5-FU SCC 2018 [47] Immunotherapy pLHMGA microparticles CD40 antibody/ CTLA4 antibody Colon carcinoma 2015 [48] Dextran/PLGA-PLA core/shell microspheres IL-2 Colon carcinoma 2013 [49] Injectable collagen-anchoring cytokines IL-2/IL-12 Melanoma/breast/colon 2019 [50] Injectable bio-responsive gel PD-L1 antibody /d-1MT Melanoma 2018 [51] Injectable alginate hydrogel Imiquimod and anti-PD-L1 with doxorubicin or oxaliplatin Breast/colon/glioma 2020 [52] Smart radiotherapy biomaterial PLGA matrix CD40 antibody/radiation NSCLC 2018 [53] Transcutaneous microneedle Patch PD1 antibody Melanoma 2016 [54] Nanofluidic drug eluting seed CD40 antibody / OX40 antibody Breast 2018 [55] Radiotherapy Radiation-linked polypeptide hydrogel depot Iodine-131 Prostate/pancreas 2016 [56] Iodine-131 CpG/ CTLA4 antibody Breast/prostate/colon/liver 2018 [57] EGFR-targeted radioactive gold nanoparticles Panitimumab and lutetium-177 Breast 2015 [58] NBTXR3…”
Section: Platformmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, ECM can be beneficial for retention of drugs in the TME. A recent study has shown that local administration of a cytokine bound to the collagen‐binding lumican with immunotherapy increases its systemic anti‐tumour effect, reducing toxicity .…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%